PERAN PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA SEBILO KECAMATAN PINO KABUPATEN BENGKULU SELATAN - Muhammad Habib (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
The development of the tourism sector is an important strategy in encouraging national and regional economic growth. The Government of Indonesia through various policies, including Undang-Undang Nomor 6 Tahun 2014 tentang Desa,, has given broad authority to villages to manage local potential independently, including the development of tourist villages. This study aims to describe the role of the Village Government in the development of Sebilo Tourism Village, Pino District, South Bengkulu Regency. Sebilo Village is one of the pioneer tourism villages that carries the concept of religious, natural, cultural, and culinary history. Through the support of village funds and local government grants, as well as the initiation of the formation of Tourism Awareness Groups, the Sebilo Village Government seeks to optimize the potential of local tourism to improve the welfare of the community. This research shows that collaboration between the village government and the community, especially the youth, is the key in transforming Sebilo Village from an ordinary bathing location to an attractive tourist destination. With a participatory approach and based on local potential, the development of tourism villages is expected to be able to encourage sustainable village economic growth and become a model for the development of tourism villages in other regions. Keywords: Village Government, Tourism Village, Community Empowerment, Sebilo, South Bengkulu.